2017
DOI: 10.1111/jgs.14894
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil‐To‐Lymphocyte Ratio: An Emerging Marker Predicting Prognosis in Elderly Adults with Community‐Acquired Pneumonia

Abstract: These results would encourage early discharge of individuals with a NLR of less than 11.12, short-term in-hospital care for those with a NLR between 11.12 and 13.4, middle-term hospitalization for those with a NLR between 13.4 and 28.3, and admission to a respiratory intensive care unit for those with a NLR greater than 28.3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
147
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(157 citation statements)
references
References 30 publications
7
147
0
3
Order By: Relevance
“…Data presented as mean (range), mean ±standard deviation, or n(%), BMI, body mass index distress syndrome, community-acquired pneumonia and sarcoidosis and tuberculosis. [13][14][15][16][17] In this study, NLR has been found to be statistically significantly higher in silicosis patients with profusion categories 2 and 3 when compared to the control group. The NLR in patients with profusion category 1 was also higher than controls; however, the difference was not significant.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Data presented as mean (range), mean ±standard deviation, or n(%), BMI, body mass index distress syndrome, community-acquired pneumonia and sarcoidosis and tuberculosis. [13][14][15][16][17] In this study, NLR has been found to be statistically significantly higher in silicosis patients with profusion categories 2 and 3 when compared to the control group. The NLR in patients with profusion category 1 was also higher than controls; however, the difference was not significant.…”
Section: Discussionsupporting
confidence: 50%
“…NLR has been shown to be an independent prognostic factor in several types of tumours, including colorectal, lung, breast, pancreatic, gastric and ovarian cancer . Studies have also shown a correlation between the NLR and the prognosis and severity of the clinical course in pulmonary diseases such as chronic obstructive pulmonary disease, acute respiratory distress syndrome, community‐acquired pneumonia and sarcoidosis and tuberculosis . In this study, NLR has been found to be statistically significantly higher in silicosis patients with profusion categories 2 and 3 when compared to the control group.…”
Section: Discussionsupporting
confidence: 49%
“…Some studies proposed the neutrophil to lymphocyte ratio (NLR) as simple and inexpensive indicators of systemic inflammation and infection. An Italian study [43] explored the performance of the NLR to predict prognosis in a cohort of 195 elderly adults with CAP. NLR predicted 30-day mortality and performed better than PSI, CURB65, CRP and white cell count to predict prognosis in the studied population.…”
Section: Biomarkers For Community-acquired Pneumonia Prognosismentioning
confidence: 99%
“…Therefore, NLCR was more sensitive than any of them alone. NLCR was used as a marker to predict the prognosis of pneumonia [13,14] and the risk of death from bacterial infection [15] had been reported. When NLCR was elevated, it might be associated with a poor clinical prognosis or an increased risk of death.…”
Section: Discussionmentioning
confidence: 99%